Respuesta :
sub -1 into the x's
[tex]f( - 1) = \frac{12}{4( - 1) + 3} [/tex]
simplify.
[tex] = \frac{12}{ - 4 + 3} [/tex]
[tex] = \frac{ - 12}{ - 1} [/tex]
awnser:
[tex]f( - 1) = - 12[/tex]
[tex]f( - 1) = \frac{12}{4( - 1) + 3} [/tex]
simplify.
[tex] = \frac{12}{ - 4 + 3} [/tex]
[tex] = \frac{ - 12}{ - 1} [/tex]
awnser:
[tex]f( - 1) = - 12[/tex]
[tex]f(x)=\dfrac{12}{4x+3}[/tex]
Substitute x = -1 to the equation of the function:
[tex]f(-1)=\dfrac{12}{4(-1)+3}=\dfrac{12}{-4+3}=\dfrac{12}{-1}=-12[/tex]
Answer: f(-1) = -12